2008
DOI: 10.1038/ejcn.2008.36
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterol consumption frequency affects plasma lipid levels and cholesterol kinetics in humans

Abstract: Background/Objectives: To compare the efficacy of single versus multiple doses of plant sterols on circulating lipid level and cholesterol trafficking. Subjects/Methods: A randomized, placebo-controlled, three-phase (6 days/phase) crossover, supervised feeding trial was conducted in 19 subjects. Subjects were provided (i) control margarine with each meal; (ii) 1.8 g/day plant sterols in margarine with breakfast (single-BF) and control margarine with lunch and supper or (iii) 1.8 g/day plant sterols in margarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 51 publications
(45 reference statements)
1
26
1
1
Order By: Relevance
“…87 Meta-analysis of these and other studies suggests that an increase in dose frequency is associated with larger decreases in LDL cholesterol.…”
Section: Phytosterol Efficacy Dose and Dose Frequencymentioning
confidence: 85%
“…87 Meta-analysis of these and other studies suggests that an increase in dose frequency is associated with larger decreases in LDL cholesterol.…”
Section: Phytosterol Efficacy Dose and Dose Frequencymentioning
confidence: 85%
“…Cholesterol absorption is a gradual process, as the ingested dietary cholesterol is secreted by the small intestine in chylomicrons that enter into the circulation during three or more subsequent postprandial periods in humans [21]. Thus, results from studies by AbuMweis et al [17,19] suggest that plant sterols are not retained in the intestinal lumen or enterocytes. In contrast, results from Plat et al [16] and Matvienko et al [18] suggest that reduction of cholesterol absorption by plant sterols can take place over a more prolonged time span rather than directly after specifi c meals.…”
Section: Plant Sterol Formulationsmentioning
confidence: 94%
“…The study by AbuMweis et al [19] showed that the consumption of 1.8 g/d of plant sterols distributed over the course of the day for 5 days lowered LDL-C by 0.21 mmol/L, whereas the consumption of the same dose once a day with breakfast did not lower LDL-C levels. The cholesterol fractional synthesis rate increased when plant sterols were consumed with each of the three daily meals.…”
Section: Plant Sterol Formulationsmentioning
confidence: 97%
See 1 more Smart Citation
“…respectively [2,3]. Interestingly, while the daily intake of cholesterol approaches that of phytosterols, plasma levels of plant sterols (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) lmol/L) and stanols (0.05-0.3 lmol/L) are markedly lower than those of cholesterol ($5 mmol/L) [4,5]. In the jejunum, both phytosterols and cholesterol are incorporated into mixed micelles and are subsequently absorbed at the apical site of enterocytes via the Niemann Pick C1 Like 1 (NPC1L1) transporter [6].…”
Section: Introductionmentioning
confidence: 94%